Comparative Study of Financial Reporting Act: The Case Study of Indonesia - Michelle Claudia; Lindawati Gani; Rafika Yuniasih (Journal of Accounting and Investment, 2021)
Research aims: This study evaluates the Indonesian Financial Reporting Bill (hereafter: Bill) and provides a recommendation to the Bill.Design/Methodology/Approach: A comparative study was carried out by comparing the Bill with Financial Reporting Acts and other related statutory from the United States of America, the United Kingdom, and twenty-seven members of the Asian-Oceanian Standard-Setters Group (AOSSG).Research findings: From the total of 24 countries, 60 documents were found, which were then manually analyzed for content and themes. Based on the study results: standard-setting board, accountant certification, and practice monitoring program were proposed to be included in the Bill.Theoretical contribution/Originality: There are few studies on the Financial Reporting Act; therefore, this study seeks to contribute to this gap.Practitioner/Policy implication: This study’s results provide insight for regulators and strengthen the accounting professions as preparers and auditors of financial statements and other related professions.Research limitation/Implication: The limitation of this research is to conduct a comparative study of the Indonesian Financial Reporting Bill with the selected countries’ Financial Reporting Acts and similar statutory.